Emerging trends in pharmacological and therapeutic potential of glycyrrhizic acids: Traditional and nanotechnological approach - Priyanka Jurel; Shiv Bahadur; Meenakshi Bajpai (Elsevier, 2024)
Introduction: Glycyrrhizic acid which is the most important active ingredient extracted from the licorice root shows great potential as a carrier material in traditional chinese medicine. Nanotechnologies hold tremendous potential as an effective drug delivery system. Recent studies have indicated that the combination of glycyrrhizic acid and nanotechnology had better therapeutic effects. Materials and methods: Literatures were searched from various databases such as PubMed, Web of Science, Scopus, Academic Journals Embase, Google Scholar and Science Direct by using keywords including like "Glycyrrhizic Acid" paired with "Traditional Chinese medicine", "Pharmacological activities", "Anti-tumor", "Anti-viral", "Hepatoprotective", "Anti-psoriatic", "Anti-Inflammatory", "Nanotechnology", or "Nanoemulsions" and their combinations, mainly from 2004 to 2024. According to the research reports, glycyrrhizic acid have a wide range of biological activities, containing anti-inflammatory, antiviral, antioxidant, gastro-protective effects, anti-obesity effects, nephroprotective effect, cardiovascular effects and hepatoprotective activity and so on. Results: This article highlights the pharmacological properties of glycyrrhizic acid and its various potential therapeutic applications. The nanoformulation including polymeric nanoparticles, solid lipid nanoparticles, phytosomes, liposomes, nanofibers, nanoemulsions, and hydrogels, have been explored to enhance their therapeutic efficacy. These formulations may offer enhanced solubility and absorption, as well as controlled and sustained release of glycyrrhizic acid. Conclusions: This review highlights on the recent studies for the pharmacological activities and therapeutic potential of glycyrrhizic acid, nanotechnology based drug delivery and major safety and toxicity issues glycyrrhizic acid also have been discussed.